Language Shattered Contemporary Chinese Poetry and Duoduo - van Crevel, Maghiel (CNWS, 1996)
Language Shattered is both a history of poetry from the People's Republic of China and a case study of the oeuvre of a leading Chinese poet. After the stifling orthodoxy of the 1950s and early 1960s, the terror of the Cultural Revolution (1966-1976) brought official Chinese literature to a total standstill. At the same time, disillusioned youths were more or less accidentally exposed to a varied body of foreign literature and began writing underground poetry. In the 1980s this poetry scene, now above ground, became one of pluriformity and proliferation in both official and unofficial circuits. The brutal suppression of the 1989 Protest Movement gave it an exile offshoot. The historical overview in Part I of this book is complemented in Part II by a discussion of Duoduo's poetry. Duoduo's career as a poet reflects the vicissitudes of Chinese Experimental poetry - and his beautiful, headstrong poems merit attention in themselves. They show that Chinese poetry is not just of interest as a chronicle of Chinese politics, but as literature in its own right.